Perancangan Infrastruktur Enkripsi End to End pada Aplikasi Penyimpanan File Berbasis Website - Ni Putu Sri Agnita Samyami Wiraputri; Cokorda Pramartha (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
The rapid evolution of information and communication technology has revolutionized how we communicate and share information. Despite the numerous benefits, these advancements have introduced challenges, particularly concerning data security and privacy. Issues like data interception and escalating file sizes necessitate effective solutions. Cryptography emerges as a pivotal tool in addressing these concerns, offering a means to bolster data security while mitigating file size. This field encompasses the science and techniques of information security, converting data into unreadable ciphertext through encryption algorithms and keys. Encryption, particularly end-to-end encryption, plays a crucial role in maintaining confidentiality during file storage and exchange. The RSA cryptographic algorithm exemplifies an asymmetric approach, utilizing distinct keys for encryption and decryption. Public and private keys ensure secure communication, with the public key encrypting messages and the private key decrypting them. This widely adopted algorithm fortifies data security across various applications. Complementing this, the Caesar Cipher, a simple substitution cryptographic technique, adds an additional layer to the encryption process. By replacing each character with another at a specified shift in alphabetical order, the Caesar Cipher offers a basic yet effective safeguard. Combining the robust RSA algorithm with the simplicity of Caesar Cipher enhances file storage security. Employing Caesar Cipher as the initial step in encryption, followed by RSA to encrypt its output, ensures double-layered encryption. This dual process guarantees that only the corresponding private key can decrypt the file, reinforcing the overall security of data storage and exchange.